Bacteriophage SPO1 development: defects in a gene 31 mutant. - Sarachu, A N (1978)
SPO1 temperature-sensitive mutant ts14-1, located in cistron 31, has a DD (DNA synthesis-delayed) phenotype at 37 degrees C and produces progeny in a stretched program. At 44 degrees C it behaves as a DO (DNA synthesis-defective) mutant and shuts off the viral RNA synthesis about 10 min after infection. The thermal sensitivity of this mutant is due to the inactivity of gp-31 (the product of gene 31) at 44 degrees C. However, gp-31 is synthesized at that temperature and partly recovers its activity at 37 degrees C. Only 5 min at the permissive temperature is enough to trigger the continuation of the phage program and to produce progeny. The partial defect at 37 degrees C and the expansion of the middle program together with the pleiotropic defects at the nonpermissive temperature could be suitable for the study of the controls involved in bacteriophage development.